2011
DOI: 10.1002/cphc.201100428
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Visualization of Surface Topography and Concentration Field by Means of Scanning Electrochemical Microscopy Using a Single Electrochemical Probe and Impedance Spectroscopy

Abstract: Scanning electrochemical microscopy visualizes concentration profiles. To determine the location of the probe relative to topographical features of the substrate, knowledge of the probe-to-sample distance at each probe position is required. The use of electrochemical impedance spectroscopy for obtaining information on the substrate-to-probe distance and on the concentration of interest using the electrochemical probe alone is suggested. By tuning the frequencies of interrogation, the probe-to-substrate distanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…Over the past several years, SECM instrumentation has been adapted and modified in order to be combined with several different techniques. Reported combinations include SECM with scanning force microscopy (SFM), 25 infrared attenuated total reflection spectroscopy, 382,383 scanning probe lithography (SPL), 50 impedance, 384 surface plasmon resonance (SPR), 319,385 scanning Kelvin probe (SKP), 386,387 scanning ion conductance (SICM), 388−391 and fluorescence microscopy. 392,393 The most used combination has been SECM with atomic force microscopy (AFM).…”
Section: Instrumental Developmentmentioning
confidence: 99%
“…Over the past several years, SECM instrumentation has been adapted and modified in order to be combined with several different techniques. Reported combinations include SECM with scanning force microscopy (SFM), 25 infrared attenuated total reflection spectroscopy, 382,383 scanning probe lithography (SPL), 50 impedance, 384 surface plasmon resonance (SPR), 319,385 scanning Kelvin probe (SKP), 386,387 scanning ion conductance (SICM), 388−391 and fluorescence microscopy. 392,393 The most used combination has been SECM with atomic force microscopy (AFM).…”
Section: Instrumental Developmentmentioning
confidence: 99%
“…However, the tip can also be switched to a potentiometric mode where the potentials generated by the ions of interest can be measured with respect to time. In recent years, several excellent publications regarding scanning ion conductance microscopy (SICM)-SECM-based studies have been reported [39][40][41][42][43][44][45] and readers are recommended to visit the references for more details. In this perspective, we have highlighted some of the SECM-only biofilm-related studies where potentiometric measurements have been used.…”
Section: Primary Principles Of Using Scanning Electrochemical Microscmentioning
confidence: 99%
“…Also, the need for simultaneous control of distance of the probe from the substrate may require two independent measurement schemes to be integrated, such as scanning of a microelectrode probe and electrochemical processing, and another measurement scheme to assess the distance of the probe from the substrate for distance control. This is the case in many SECM experiments, except when the same microelectrode probe is used for both the electrochemical measurement and assessing distance using electrochemical impedance spectroscopy [ 36 ]. Lateral hydrodynamic drag of small volumes of the solution by the scanned microprobe can cause flow artifacts in SECM.…”
Section: Resultsmentioning
confidence: 99%